2023
DOI: 10.3846/ijspm.2023.20563
|View full text |Cite
|
Sign up to set email alerts
|

How Do Different Noise Pollution Sources Affect Apartment Prices?

Radoslaw Trojanek

Abstract: The paper analysed the impact of different noise sources on the residential market. This research used the hedonic method in OLS, SAR and SEM models based on the data set containing geocoded 16,247 apartments in Poznan. Strong evidence was found that noise is negatively linked with apartment prices. The apartment prices were the most significantly influenced by railway noise – an increase of 1 dB above 55 dB causes a 1.79% decrease in the value of an apartment. For other noise sources, aviation noise had the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The locational attributes are made up of characteristics relating to the proximity of the property to amenities. Among the locational attributes most often studied in the literature are distance to public transport services [36], schools [11,13], hospitals [33], and green areas [22,37,38]. Finally, the qualities of the neighborhood refer to the characteristics of the neighborhood or surrounding area that can affect the price of the property.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The locational attributes are made up of characteristics relating to the proximity of the property to amenities. Among the locational attributes most often studied in the literature are distance to public transport services [36], schools [11,13], hospitals [33], and green areas [22,37,38]. Finally, the qualities of the neighborhood refer to the characteristics of the neighborhood or surrounding area that can affect the price of the property.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It is considered an important convenience for many consumers, especially in densely populated urban areas, as it can affect the perception of the property's safety and convenience. Kryvobokov et al [46] and Trojanek [38] highlight the positive aspect of the presence of a garage in rental and sale properties, respectively. Islam et al [20] found that, in general, the presence of a garage increases the rental price of a home by 15% and, analyzing by planned and unplanned areas, they found that the presence of garages in planned areas has a greater impact than in unplanned areas.…”
Section: Structural Attributesmentioning
confidence: 99%
See 1 more Smart Citation